The influence of micro-nano Ti2AlC on the hot deformation behavior of TiAl alloys. (October 2022) - Wang, Yupeng; Ma, Tengfei; Li, Lei; Liu, Chengze; Zhang, Yusheng; Zhou, Lian
Abstract: To strengthen TiAl alloys, micro-nano Ti2 AlC precipitates were fabricated in situ by spark plasma sintering using Ti–48Al–2Nb–2Cr pre-alloyed powder and multilayer graphene oxide. The effect of micro-nano Ti2 AlC precipitation on the hot deformation behavior of Ti–48Al–2Nb–2Cr alloy was systematically studied at 1100, 1150, and 1200 °C under strain rates of 0.01, 0.1, and 1 s −1 . The fully lamellar structure was transformed to a nearly lamellar structure when the graphene content was increased. In addition, the lamellar colony size significantly decreased and the number of Ti2 AlC particles increased with increasing graphene content. The hot deformation results show that the flow stress of the Ti2 AlC–TiAl composites first increased and then decreased with increasing graphene content, reaching the maximum with the addition of 0.3 wt% graphene. Micro-nano Ti2 AlC particles hindered dislocation slip, leading to a strengthening effect. However, Ti2 AlC particles promoted dynamic recrystallization through grain refinement and dislocation pile-up, resulting in a softening effect. The strengthening and softening effects of the Ti2 AlC–TiAl composites depend on the Ti2 AlC particle content. Highlights: Ti2 AlC phase induces refinement strengthening and hinders dislocation slip leading to strengthening effect. Ti2 AlC phase promotes DRX by grain refinement and dislocation pile-up resulting in softening effect. The strengthening and softening effect of Ti2 AlC–TiAl composite depends on the content of Ti2 AlC particles.